A single procedure for the registration of maxillo-mandibular relationships and alignment of intraoral scans of edentulous maxillary and mandibular arches. Issue 1 (January 2020) - Lo Russo, Lucio; Caradonna, Giammarco; Salamini, Angelo; Guida, Laura
Abstract: Purpose: The presented technique describes the intraoral scanning workflow to capture scans of edentulous arches and occlusion rims, align them as per maxillo-mandibular relationships registered in the occlusion rims, and incorporate data for tooth arrangement. Methods: On preliminary intraoral scans of the edentulous arches, design the baseplates for the occlusion rims, make a 3D print of them and finalize by adding wax. Use occlusion rims to make jaw relation record and definitive intraoral scans. Use the "Pre-preparation scan" function to link scans of occlusion rims to scans of edentulous arches and align each other. Conclusions: Making and aligning, in a single procedure, intraoral scans of the edentulous arches and occlusion rims incorporating maxillo-mandibular relationships and information for tooth arrangement, allow to proceed directly with the denture design, thus, being sensible from the treatment time efficiency point of view. The technique is applicable to both partial and complete edentulous maxillary and mandibular arches. Nonetheless, care should be taken in stabilizing occlusion rims, whose shape is characterized by a reduction in size of the baseplates. In addition, its accuracy in comparison with the current clinical best practice based on conventional procedure requires to be addressed by further research.